STRATEGI PEMIMIPIN LEMBAGA PENDIDIKAN NONFORMAL DALAM MENINGKATKAN JUMLAH PESERTA DIDIK PADA MASA PANDEMI COVID 19 (STUDI KASUS DI YAYASAN GRIYA AL QUR’AN SURABAYA): id - Ahmad Abdur Rokhim (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2022)
AbstracThe Covid-19 pandemic has made many non-formal educational institutions experience a decrease in the number of students and even go out of business. This is due to community activities that are mostly carried out at home as an effort to prevent the transmission of the Covid-19 Virus. To maintain the existence of an educational institution, it is necessary to increase the number of students, because the existence of an educational institution depends on the existence of its students. To realize this, creative and innovative leaders are needed to determine strategies to increase the number of students during the Covid-19 pandemic. This study aims to determine the strategy of leaders of non-formal education institutions in increasing the number of students during the Covid-19 pandemic. This research was conducted at the Griya Al Qur'an Foundation Surabaya. The approach used in this research is a descriptive qualitative approach using field research methods. The results of this study reveal that the steps taken by the Operational Director of Griya Al Qur'an as the head of the institution in determining strategies to increase the number of students during the Covid-19 pandemic include the process of analysis, planning, organizing, implementing and monitoring. The strategies used are: 1) conducting social media campaigns, 2) providing online registration and learning, 3) collaborating with mosques, government institutions, companies or recitation communities, 4) holding the "Student Ambassador" program, 5) reducing costs. education, 6) providing online guidance services, 7) organizing social activities, 8) promoting through conventional print media, and 9) promoting through radio.